PRECIPITATING FACTOR KEJADIAN SKABIES PADA SANTRI PONDOK PESANTREN AL-MU’AWANAH MALNU MENES - Nurjaman, Nurjaman; Mujiyanti, Sri; Sumiati, Sumiati; Marwiyah, Nila (STIKes Kharisma Persada, 2024)
Scabies is an infectious disease caused by the bacterium Sarcoptes scabiei variant hominis and is transmitted directly or indirectly. This study aims to find out what are the factors that precipitating the incidence of scabies in students at Islamic boarding schools. And using a quantitative method with a descriptive analytic research design that uses a cross sectional approach. Data collection used a questionnaire using total sampling which involved 124 class 1 student respondents at the Al-Mu'awanah Malnu Menes Islamic Boarding School. The results showed that almost half of the respondents were women and with an average age of 12 years. There are 87 students with poor knowledge (70.2%). There are 78 students with bad attitudes (62.9%). There are 77 students who have less personal hygiene (62.1%). And most of the pesantren environmental sanitation is not supportive, namely 97 (78.2%). The results of the bivariate analysis test found that the knowledge variable obtained a p-value of 0.003, which means that there is a relationship between knowledge and the incidence of scabies, attitude with a p-value of 1.000, personal hygiene with a p-value of 0.210 and environmental sanitation with a p-value of 0.407 which means that these three variables have no relationship to the incidence of scabies. The results of this study are expected to be a reference material for Islamic boarding schools to always maintain and pay attention to personal hygiene and environmental sanitation.AbstrakScabies merupakan penyakit menular yang disebabkan oleh bakteri sarcoptes scabiei varian hominis dan ditularkan secara langsung maupun tidak langsung. Penelitian ini bertujuan untuk mengetahui apa saja faktor-faktor yang mencetuskan kejadian Skabies pada santri di pondok pesantren. Dan menggunakan metode kuantitatif dengan desain penelitian deskriptif analitik yang menggunakan pendekatan cross sectional. Pengumpulan data menggunakan kuesioner dengan menggunakan total sampling yang melibatkan124 responden santri kelas 1 di pondok Pesantren Al-Mu’awanah Malnu Menes. Hasil penelitian menunjukan bahwa hampir setengah dari responden adalah perempuan dan dengan rata-rata usia 12 tahun. Santri yang berpengetahuan kurang baik sebanyak 87 (70,2%). Santri dengan sikap yang buruk sebanyak 78 (62,9%). Santri yang memiliki personal hygiene kurang sebanyak 77 (62,1%), sebagian besar sanitasi lingkungan pesantren kurang mendukung, yaitu 97 (78,2%). Hasil uji analisis bivariat didapatkan bahwa variabel pengetahuan memperoleh nilai p-value 0,003 yang artinya terdapat hubungan antara pengetahuan dengan kejadian scabies,, sikap dengan nilai p-value 1,000, personal hygiene dengan nilai p-value 0,210 dan sanitasi lingkungan dengan nilai p-value 0,407 yang artinya ketiga variable tersebut tidak memiliki hubungan terhadap kejadian skabies. Hasil penelitian ini diharapkan bisa menjadi bahan acuan bagi pihak pondok pesantren untuk selalu menjaga dan memperhatikan sikap personal hygiene dan sanitasi lingkungan.